ANALISIS KUNJUNGAN ULANG WISATAWAN NUSANTARA DENGAN MODEL KONSTRUK BERHIERARKI - HERAYANTHI W., DWI; SUKARSA, KOMANG GDE; OKA, TJOKORDA BAGUS; KENCANA, EKA N. (E-Jurnal Matematika; Vol 5 No 4 (2016)DO - 10.24843/MTK.2016.v05.i04.p140, 2016)
This research is aimed to analyze the effect of domestic tourists’ satisfaction towards their intention to revisit destinations at Badung Regency, Province of Bali by using hierarchical construct modeling. Data from 75 local tourists were collected in July through December 2015 and were used to model this causal relationship.  In our model, destination attributes, tourist’s facilities, and destination accessibilities were positioned as the second-order constructs and proposed have effect on tourists’ satisfaction.  Futhermore, satisfaction – in turns – is proposed affects tourist intention to revisit.  We found destination attributes significantly affect tourist satisfaction with its causal value is 0.410 and this satisfaction significantly affects their intention to revisit tourism destinations at Badung Regency with path value as much as 0.764.
Keywords: hierarchical construct model, intention to revisit, tourist satisfaction